Performance of 3 mL versus 5 mL Discarded Volume for Blood Sampling from Central Venous Access Device - Lalthanthuami, HT; Kumari, MJ; Venkateswaran, R; Lakshmi, PR; Ramamoorthy, Lakshmi (Journal of Laboratory Physicians, 2021)
Background Central venous access devices (CVAD) are an essential part of safe practices in critical care, which enable effective venous access and help in avoiding repeated venipuncture. Discard method is widely practiced for blood sampling. A single occasion of blood sampling may cause minimal blood loss; however, the cumulative volume sequential sampling may become clinically signiﬁcant. The study aims to reduce diagnostic blood loss, ensuring that the subsequent blood sample is not diluted or contaminated by residual intraluminal ﬂuid.Patients and Methods Within-subjects comparative design was adopted for 64 adult patients in the medical intensive care unit of a tertiary hospital. Two blood samples, using 3 mL and 5 mL discarded volume methods, were collected from each patient. Six serum parameters were measured on each of the paired samples and compared.Statistical Analysis Used Paired t-test and Wilcoxon signed rank test were used for comparing the two methods. Bland–Altman plot analysis and intraclass correlation were used for clinically meaningful analysis.Results When tested for fixed bias, there is no statistically significant difference between the methods. Potassium and creatinine levels showed significant proportional bias. The agreement limits of sodium, potassium, creatinine, and direct bilirubin were outside the clinically accepted interval, but the proportion of samples outside these intervals was less than 10%. All serum parameters showed excellent reliability, except for sodium which demonstrated good reliability.Conclusions The practice of discarding 3 mL of blood for discard method is suggested, instead of the standard 5 mL to reduce iatrogenic blood loss. Thus, nurses in critical care are uniquely positioned to limit the diagnostic blood loss while obtaining blood samples.
Keywords: blood discards; discarded volume; blood sampling; critical care; central lines; central venous access device; diagnostic blood loss